Analisis Hubungan Konsentrasi dan Aktivitas Antimikroba Ekstrak Kayu Secang (Caesalpinia sappan L.) Cair serta Serbuk - Widodo, Tanty Sulistiani; HK, Lenny Amelia (Ma'soem University, 2025)
Preservation techniques have been widely applied in food processing. One of the commonly used methods is the addition of synthetic chemical substances, but this can have negative impacts on human health and the environment. Therefore, there is a need for alternative natural preservatives, such as sappan wood (Caesalpinia sappan L.). Sappan wood is a plant species that can be utilized as a natural preservative in food products and possesses various biological benefits, including anti-inflammatory, antioxidant, antivirus and antibacterial properties. This study aims to analyze the relationship between the concentration of sappan wood extract and its antimicrobial activity, as well as to compare the effectiveness of liquid and powder extracts in inhibiting microbial growth. The research employed a Simple Linear Regression method, where variable X represented the concentration of sappan wood extract (%) and variable Y represented the inhibition zone diameter of microbial growth (mm), with concentrations of 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80%. Based on the results of antimicrobial activity testing, both liquid and powdered sappan wood extract exhibited strong antimicrobial activity, indicating potential as a natural preservative. The effectiveness of the extract in inhibiting microbial growth increased with higher extract concentrations. This finding demonstrates a strong and positive linear relationship between extract concentration and microbial growth inhibition.